Edukasi Pola Hidup Bersih dan Sehat (PHBS) pada Anak Usia Sekolah Dasar melalui Media Permainan Berbasis Kearifan Lokal "BAREGA” di Kelurahan Marang Kota Palangka Raya: Education Clean and Healthy Behaviour (PHBS) in Children of Elementary Schools using Media Local Wisdom Games “BAREGA” at Marang Urban Village of Palangka Raya - Trilianty Lestarisa; Elsa Trinovita; Angeline Novia Toemon (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Clean and Healthy Living Behavior (PHBS) is an effort to create conditions for individuals, families, groups, and communities in attitudes and behavior so they can adopt a healthy life to maintain and improve their health status. Elementary school-age children often ignore the health problems they experience, so preventive and promotive efforts are needed so that they have good and correct PHBS knowledge, attitudes, and actions to prevent some health problems from occurring. Health education for children aims to familiarize them with a clean and healthy lifestyle that starts with being responsible for their health and environment. This education can be done by using learning methods adapted to the characteristics and needs of children. Therefore, the Community Service Team carries out community service activities as an effort to increase education regarding PHBS, an innovative media based on local wisdom, namely the game "BAREGA," with the primary target audience being elementary school-age children through counseling and demonstrations on a combination of puzzle games and snake's ladders with a material clean and healthy lifestyle based on local wisdom. The implementation of this activity went smoothly, all the children looked very enthusiastic, and it was hoped that it would increase public awareness, especially among children, in implementing a clean and healthy lifestyle in everyday life.